Hands-on genetic algorithms with Python applying genetic algorithms to solve real-world deep learning and artificial intelligence problems - Wirsansky, Eyal (Packt Publishing Ltd, 2020)
Using this book, you will gain expertise in genetic algorithms, understand how they work and know when and how to use them to create intelligent Python-based applications. By the end of this book, you will have hands-on experience applying genetic algorithms to artificial intelligence as well as numerous other domains.